2021
DOI: 10.37616/2212-5043.1261
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation Used in Acute Respiratory Distress Syndrome with COVID-19: A Systematic Review and Meta-Analysis

Abstract: Introduction Protective pulmonary mechanical ventilation, higher positive end-expiratory pressure, neuromuscular blockade, prone positioning, and pulmonary recruitment procedures are all strategies in severe COVID-19 cases. Extracorporeal Membrane Oxygenation (ECMO) can be seen as an alternative to traditional treatment in certain patients when conventional therapy fails. We present a study that intends to systematically review and meta-analysis ECMO use in COVID-19 patients. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Previous meta-analyses have compared the effect of the presence or absence of ECMO use on COVID-19 mortality or the difference in mortality between COVID-19 and other virus-induced diseases treated with ECMO [7,77,[104][105][106]. For example, Kusumawardhani's study found a significantly higher incidence of mortality in COVID-19 patients treated with ECMO compared to those not treated with ECMO (OR = 15.79, 95% CI: 4.21-59.28, p < 0.0001) [106]. Ramanathan's meta-analysis reported an in-hospital ECMO mortality rate of 37.1% for COVID-19 patients, which is similar to that of patients with non-COVID-19-related ARDS [7].…”
Section: Comparison With Prior Meta-analysismentioning
confidence: 99%
“…Previous meta-analyses have compared the effect of the presence or absence of ECMO use on COVID-19 mortality or the difference in mortality between COVID-19 and other virus-induced diseases treated with ECMO [7,77,[104][105][106]. For example, Kusumawardhani's study found a significantly higher incidence of mortality in COVID-19 patients treated with ECMO compared to those not treated with ECMO (OR = 15.79, 95% CI: 4.21-59.28, p < 0.0001) [106]. Ramanathan's meta-analysis reported an in-hospital ECMO mortality rate of 37.1% for COVID-19 patients, which is similar to that of patients with non-COVID-19-related ARDS [7].…”
Section: Comparison With Prior Meta-analysismentioning
confidence: 99%
“…In normal humans, initial toxic effects appear after 10 h of 1 ATA oxygen exposure. The clinical picture is divided into three phases, namely: (a) tracheobronchitis, (b) ARDS, and (c) pulmonary interstitial fibrosis [ 18 , 20 , 33 ]. Oxygen can be tolerated above sea level for about 24–48 h without severe tissue damage.…”
Section: Lung Toxicitymentioning
confidence: 99%